Hierarchical-level failure analysis for CFRC lattice stiffened panel. (February 2023) - Bao, Wenyi; Li, Ming; An, Xiyue; Han, Han; Lou, Yunfeng; Fan, Hualin
Abstract: A hierarchical-level failure analysis method from carbon fiber reinforced composite (CFRC), unit-cell lattice to lattice stiffened component was developed to predict the failure load of lattice stiffened panels. A nondestructive method was applied to identify the composite parameters of lattice ribs. Axial compression experiments were carried out to reveal the failure pattern and load of unit-cell lattice and lattice-stiffened panels. Compared with the standard unidirectional laminate strength, these component failure analyses suggest knock-down factors (KDFs) to include the attenuation effect of the rib node intersection. The failure loads of CFRC lattice stiffened panels were predicted by the KDFs. The research lays a good foundation to design and manufacture large-sized CFRC lattice structures. Highlights: A hierarchical-level failure analysis method for lattice stiffened structure was proposed. The method is based on hierarchical-level testing and data processing. The hierarchical-level failure analysis method can control predication error within 10%.